Analysis of Lattice Constant, Structure and Crystal Size of TiO2/Rough Bamboo Acitivated Carbon Nanocomposite Using Mass Variation - Hifzi, Zudiya; Darvina, Yenni (Department of Physics, Universitas Negeri Padang, 2024)
Energy storage materials such as rechargeable batteries: cameras, cellphones, laptops, and others, are often used for daily needs. The working indicator of the battery is energy storage capacity, which depends on anode material. Generally, battery anodes are made from graphite but have limited energy capacity, which causes frequent overheating. One of the factors that influences energy storage capacity is surface area of the anode, where the smaller the particle size, the greater the storage capacity. So, research was carried out on materials that could replace graphite as an anode material for rechargeable batteries by having superior properties. This material is TiO2/Rough bamboo activated carbon nanocomposite. Nanocomposites will be synthesized using the sol-gel method and then analyzed using XRD to obtain information about lattice constants, structure, and crystal size. So, this research aims to determine the lattice constant, structure, and crystal size of the forming materials such as carbon, activated carbon and TiO2, and the TiO2/Activated carbon nanocomposite. Nanocomposites will be synthesized with mass variations to see the superior properties of the two forming materials. Variations were carried out with mass ratios of TiO2 and activated carbon, respectively, namely 40%:60%, 50%:50%, and 60%:40%. This research shows that the lattice constant in each variation has results that are by the shape of the crystal structure, and the crystal size value of the nanocomposite has reached the requirements as a nanocomposite material, namely a size below 100 nm. Activated carbon appears to have superior properties for smaller particle sizes than TiO2.